Perancangan Hazard Identification, Risk Assessment, And Determining Control (HIRADC) Di Schneider Electric Cikarang - Jonathan Christanto Handoko; Jani Rahardjo (Jurnal Titra, 2017)
Occupational Health and Safety plays a crucial role in all companies or oganizations. The Indonesian Regulations of Occupational Health and Safety have been embroidered on UU No. 1 of 1970, which have been explicitly applied in all the Indonesian companies or oganizations. HIRADC is often used by management to resolve the issue of Occupational Health and Safety. HIRADC is divided into three parts: Hazard Identification, Risk Assessment, and Determining Control. HIRADC, which is annually reviewed and updated by the management, discovers and controls the potential hazards that exist around the working environment. It goes in line with OSHAS 18001:2007 and ISO 14001:2004.